Research on Finsler metric in KNN algorithm - Chen, Ming; He, Shuping; Li, Fanzhang (Jisuanji Kexue yu Tansuo / Journal of Computer Science and Frontiers, 2011)
In order to overcome the shortcomings of traditional K nearest neighbor (ANN) algorithms in distance definition, this paper proposes a new KNN algorithm based on Finsler metric, FMKNN. The algorithm defines the distance between sample points as the Finsler metric and preserves the distance between sample properties, making the distance between sample points more general. The experiment on handwritten data sets shows that, the classification accuracy of FMKNN algorithm is higher than traditional KNN algorithms.